Evaluating the Maturity and Obstacle Factors Affecting the Sichuan-Tibet Tourism Corridor, China - Li Mi; Xi Jianchao; Ye Sui; Li Ziqiang; Huang Tai (Redai dili)
Tourism corridors are a new type of activity carrier with the advent of self-driving tours and transportation integration in tourism. Tourism corridors can help to reconstruct spatial tourism patterns and optimize regional tourism industry structures. Performing tourism corridor maturity assessments can be used to guide corridor construction. However, few studies have included both linear corridor maturity assessments and obstacle factors. Using the entropy weight method and obstacle degree model, we constructed an evaluation index system for the Sichuan-Tibet tourism corridor maturity based on four aspects: resource endowment, reception level, infrastructure, and security guarantee. The obstacle factors of the corridor were combined with the results obtained from the evaluation system and discussed. The Sichuan-Tibet tourism corridor is currently at a relatively low maturity level and sections with low maturity levels and below account for 89.04% of the total mileage. Owing to the fact that the economic development level of Tibet lags behind that of Sichuan, as well as the geographical complexity, the low maturity sections were mostly concentrated in Tibet. The maturity of the tourism corridor exhibited a "high-low-high" spatial distribution, in which the high-maturity regions were located in Chengdu and Lhasa at both ends of the corridor. In contrast, the low-maturity regions were mainly concentrated in the Bomi-Mangkang and Litang-Yajiang sections in the central part of the corridor. The main obstacles to the maturity of the Sichuan-Tibet tourism corridor had effects that decreased in the order of reception level > infrastructure > security guarantee > resource endowment. Based on the specified indicators, service facilities, tourist catering, medical level, entertainment facilities, and communication conditions were the main obstacles. The main obstacle factors in each section of the tourism corridor differed and were divided into resource obstacle, reception facility obstacle, and security obstacle sections. Among these, security obstacle factors were present in most sections. Sections with differing obstacles should therefore take measures according to local conditions to reduce the impacts of their obstacles. This study addressed the spatial evaluation of linear corridor development and construction, which can be used to evaluate the maturities of other tourism corridors and provide support for the development and construction of the Sichuan-Tibet tourism corridor.